Human whole genome genotype and transcriptome data for Alzheimer’s and other neurodegenerative diseases - Allen, Mariet; Carrasquillo, Minerva M.; Funk, Cory; Heavner, Benjamin D.; Zou, Fanggeng; Younkin, Curtis S.; Burgess, Jeremy D.; Chai, High-Seng; Crook, Julia; Eddy, James A.; Li, Hongdong; Logsdon, Ben; et al. (Scientific data, 2016)
Previous genome-wide association studies (GWAS), conducted by our group and others, have identified loci that harbor risk variants for neurodegenerative diseases, including Alzheimer's disease (AD). Human disease variants are enriched for polymorphisms that affect gene expression, including some that are known to associate with expression changes in the brain. Postulating that many variants confer risk to neurodegenerative disease via transcriptional regulatory mechanisms, we have analyzed gene expression levels in the brain tissue of subjects with AD and related diseases. Herein, we describe our collective datasets comprised of GWAS data from 2,099 subjects; microarray gene expression data from 773 brain samples, 186 of which also have RNAseq; and an independent cohort of 556 brain samples with RNAseq. We expect that these datasets, which are available to all qualified researchers, will enable investigators to explore and identify transcriptional mechanisms contributing to neurodegenerative diseases. Design Type(s) disease state design • individual genetic characteristics comparison design Measurement Type(s) genetic sequence variation analysis • transcription profiling by array assay Technology Type(s) Whole Genome Association Study • RNA-seq assay Factor Type(s) regional part of brain • diagnosis Sample Characteristic(s) Homo sapiens • cerebellum • temporal cortex Machine-accessible metadata file describing the reported data (ISA-Tab format)